Bilateral pulmonary sequestrations mimicking advanced lung malignancy - Poh, Mau Ern; Ng, Wei Lin; Liam, Chong Kin; Mohd Ramli, Norlisah; Hashim, Shahrul Amry (AME Publishing Company, 2018)
Bilateral pulmonary sequestrations are extremely rare and uncommonly diagnosed during adulthood. It can present with severe symptoms such as hemoptysis. It can also be misdiagnosed as a primary lung malignancy.